Struktura organizacyjna Zielonogórskiej i Gorzowskiej Chorągwi ZHP w latach 1975-1989 = Organization structure of Zielona Góra and Gorzów Scout Divisions over the period of 1975-1989 - Bartkowiak, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The administration reform that divided Poland in to 49 states caused also changes in the structure of the Polish Scouts, e.g. the creation of new divisions - among others in Zielona Góra and Gorzów. Over the period of 1975-1989, when the country was still referred to as the People's Republic of Poland, the two divisions operared on the territories of the states of "zielonogórskie" and "gorzowskie". Their organization structures were built after 1975 and their membership figures peaked in the second half of 1970's, which was brought to a sudden end in 1981 when considerable numbers quit - most likely due to the political situation in the country (martial law) and accompanying social attitudes. Over the period of 1983-1988 the declining tendency grew weaker but the membership figures were never so high as before.
Keywords: Związek Harcerstwa Polskiego; Zielona Góra (okręg) - organizacje; Gorzów Wielkopolski - organizacje; historia - 1945-1989